'We have to be really careful': policy intermediaries preventing violent extremism in an era of risk. Issue 3 (4th May 2022) - Baak, Melanie; Stahl, Garth; Schulz, Samantha; Adams, Ben
ABSTRACT: In the field of preventing and countering violent extremism (P/CVE) schools have an important role to play, but precisely how policy actors and educators should best respond to extremism within their schools remains uncertain. Reporting on data from a broader study, this article draws on semi-structured interviews with three participants. The participants were working as policy intermediaries responsible for implementing a federally funded, small-scale grant to develop a program in four Australian schools intended to guard against student behaviours deemed 'at risk' of leading to violent extremism. Investigating the strategies and negotiations of these policy intermediaries, we demonstrate the politicization of policy enactment in the field of P/CVE. We draw on Beck's work to understand the discourses of risk that underpin the P/CVE space and to focus on the strategic negotiations of these policy intermediaries as responses to various forms of risk. The findings contribute to understandings of 'risk management' in a neoliberal state particularly in the development and enactment of policy in education, through a focus on how policy intermediaries operate in an 'in-between' space between federal prerogatives and local constraints.